Psoriasis and Psoriatic Arthritis-Related Uveitis: Different Ophthalmological Manifestations and Ocular Inflammation Features. (2nd November 2017) - Abbouda, Alessandro; Abicca, Irene; Fabiani, Claudia; Scappatura, Nicolò; Peña-García, Pablo; Scrivo, Rossana; Priori, Roberta; Paroli, Maria Pia
ABSTRACT: Purpose : To compare clinical features of uveitis in patients affected by psoriasis and psoriatic arthritis (PsA). Methods : A retrospective case-control study. Results : 117 patients were affected by uveitis and psoriasis or PsA (92 and 25 patients, respectively) from 2003 to 2013. Axial PsA was associated with unilateral uveitis onset compared to the peripheral pattern (p < 0.03). The prevalence of eyes with at least one complication involving anterior segment was significantly more represented in the PsA group than the psoriasis one (p = 0.024). Anterior segment complications were more frequently associated with posterior ones in PsA patients than in psoriasis patients (p = 0.005). Most common complications in total sample at baseline examination were cataract (29.7%), ocular hypertension (17%), macular edema (7%), and pupillary seclusion (4.4%). Conclusion : Uveitis in patients with psoriasis and PsA may have distinguishing clinical features. PsA patients have more ocular complications than those with psoriasis. Both groups need an ophthalmological examination to promptly detect ocular co-morbidity.